2000
DOI: 10.1016/s0008-6363(00)00046-8
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol modulates endothelin-1 expression and release in human endothelial cells

Abstract: Objective: In this study the role of 17b-estradiol (E2) in the regulation of endothelin-1 (ET-1) mRNA expression and secretion was investigated in cultured human umbilical vein endothelial cells (HUVECs). Methods: Endothelial cells were either deprived of or treated 29 27with 17b-estradiol (10 , 10 M) for 48 h. After the incubation, the effect of E2 on ET-1 gene expression was evaluated by Northern blot analysis. ET-1 release into the media was measured by radioimmunoassay after 6 h of incubation under basal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 32 publications
2
37
1
2
Order By: Relevance
“…Such polar secretion occurs in endothelial cells (33), and is likely critical to the role of ET-1 as a paracrine/autocrine mediator. We found that AEC produce ET-1 at levels comparable to those of endothelial cells (34,35). In addition, AEC-associated ET-1 was detected predominantly in the cytoplasm by immunocytofluorescence, and some ET-1 immunoreactivity was also detected in the nucleus.…”
Section: Discussionmentioning
confidence: 62%
“…Such polar secretion occurs in endothelial cells (33), and is likely critical to the role of ET-1 as a paracrine/autocrine mediator. We found that AEC produce ET-1 at levels comparable to those of endothelial cells (34,35). In addition, AEC-associated ET-1 was detected predominantly in the cytoplasm by immunocytofluorescence, and some ET-1 immunoreactivity was also detected in the nucleus.…”
Section: Discussionmentioning
confidence: 62%
“…Estrogen also inhibits the endothelin release from endothelial cells in bovine artery 75 and human umbilical vein 76 which may contribute to prevent circulatory failure. This is at least partly mediated by the inhibition of mitogen-activated protein kinase activity.…”
Section: Inhibition Of Vasoconstrictive Reactionmentioning
confidence: 99%
“…Endothelial cells cover the lumen of blood vessels and play an essential role in the regulation of vessel homeostasis and of flow and blood pressure in the circulatory system [17,18]. The endothelium is a dynamic system that is able to respond to different physical and chemical conditions through the production of many vasoactive substances such as endothelins (ETs), prostaglandin and nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 99%